Climate Change and Greenhouse Gas Mitigation: Challenges and Opportunities for Agriculture - Paustian, Keith; Babcock, Bruce A.; Hatfield, Jerry; Kling, Catherine L.; Lal, Rattan; McCarl, Bruce A.; McLaughlin, Sandy; Mosier, Arvin R.; Post, Wilfred M.; Rice, Charles W.; Robertson, G. Philip; Rosenberg, Norman J.; et al. (Council for Agricultural Science and Technology (CAST), 2004)
Greenhouse gases (GHGs) are of increasing concern because of their potential role in promoting rapid and undesirable change in climate. Agriculture ironically serves as both a source and a sink for this increase in GHGs. This report analyzes agriculture’s complex, pivotal role in this vitally important issue by considering policy options, implementation, and future monitoring and verification of GHG mitigation. The report outlines seven potential methods for agricultural mitigation of GHG concentrations.